The Influence Of Organizational Commitment And Work Motivation On Employee Performance In The Regional Financial And Asset Management Agency (BPKAD) Lampung District - Jayanti , Waya Tri; Josiah , Trisnowati (Utami Publisher, 2025)
This study aims to find the effect of organizational commitment and work motivation on employee performance at the Regional Financial and Asset Management Agency (BPKAD) of North Lampung Regency. The type of research used in this study is a quantitative research model. This study used 40 research respondents. There are three variables in this study, namely 2 independent variables X1 and X2 and 1 dependent variable Y. Based on the results of data analysis, the answer to the hypothesis was found as follows; there is an influence of the organizational commitment variable (X1) on the employee performance variable (Y), with an influence level (R-square) of 47.9%. There is an influence of work motivation variable (X2) on employee performance variable (Y), with an influence level of 66.6%. There is an influence of organizational commitment variable (X1) and work motivation variable (X2) together on employee performance variable (Y), with an influence level of 67%. Based on data analysis through hypothesis testing both partially and simultaneously, it is stated that each independent variable has an influence on the dependent variable and there are things that need to be improved in order to improve employee performance in order to achieve organizational goals.